2022
DOI: 10.1002/fsn3.2949
|View full text |Cite
|
Sign up to set email alerts
|

Multiple responses optimization of antioxidative components extracted from Fenugreek seeds using response surface methodology to identify their chemical compositions

Abstract: Fenugreek seeds (Trigonella foenum‐graecum L.), one kind of traditional Chinese medicine, are reported to be of great potential as a new alternative in terms of their bioactive components. In our present study, an ultrasonic‐assisted method was applied in the extraction of antioxidative components from fenugreek seeds. Four factors: ethanol concentration, liquid–solid ratio, sonication time, and sonication power were selected and multiple responses were studied using the response surface methodology (RSM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The contents of geniposide ( 1 ) ranged from 4.82 to 7.50 mg/ml, which conformed to quality standard of LQL (not less than 2.50 mg/ml). In addition to the quality control compound, other high‐content compounds were also reported to present promising antiviral and anti‐inflammatory effects, which may be closely related to the efficacy of LQL 32–40 . For example, stachyose ( 44 ) could alleviate acute colitis in mice by increasing beneficial microbiota and bacterial diversity, which might be a new potential way to ulcerative colitis patients 32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contents of geniposide ( 1 ) ranged from 4.82 to 7.50 mg/ml, which conformed to quality standard of LQL (not less than 2.50 mg/ml). In addition to the quality control compound, other high‐content compounds were also reported to present promising antiviral and anti‐inflammatory effects, which may be closely related to the efficacy of LQL 32–40 . For example, stachyose ( 44 ) could alleviate acute colitis in mice by increasing beneficial microbiota and bacterial diversity, which might be a new potential way to ulcerative colitis patients 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Group A contained 15 compounds (compounds 3-7, [20][21][37][38][39][40][41][42][43] with IS1 (50.0 ng/ml) and IS2 (7.0 ng/ml). Group B comprised 25 compounds (compounds 9-19, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] with IS1 (50.0 ng/ml) and IS3 (50.0 ng/ml). Group C included four compounds (compounds 1, 2, 8, and 44) with IS1 (50.0 ng/ml) and IS3 (50.0 ng/ml).…”
Section: Standard Solution and Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study identified flavonoid glycosides in fenugreek seeds, and the main flavones were apigenin adducts, followed by luteolin derivatives [ 5 ]. Another study also identified astragalin and apigenin-7-O-β-D-glucoside in fenugreek seeds by liquid chromatography–mass spectrometry (LC–MS) analysis [ 23 ]. Taken together, these studies showed that flavonoids and related derivatives may be the main secondary metabolites in fenugreek.…”
Section: Discussionmentioning
confidence: 99%